[Discussion of a Prediction of Business Failure Using Accounting Data]: A Reply - Wilcox, Jarrod W. (Journal of Accounting Research, 1973)
Jarrod W. Wilcox, [Discussion of a Prediction of Business Failure Using Accounting Data]: A Reply, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 188-190